Expressão heteróloga de uma osmotina laticífera e desenvolvimento de protocolos para extração da proteína recombinante a partir de corpos de inclusão - Nascimento, Camila Tauane Monteiro do (2016)
In the previous step to this work, a protein identified as osmotin (CpOsm) was purified from Calotropis procera latex which showed strong antifungal activity. The protein was expressed in prokaryotic and eukaryotic systems, but a suitable protocol for purification has not been achieved. In the present work, from inclusion bodies (IB) obtained from Escherichia coli BL21 (DE3) proceeded to a survey by different solubilization protocols of proteins in an attempt to obtain the recombinant protein (rCpOsm) soluble, and then evaluates it as its activity and finally, exploring new methods for purification. The bacterial culture was induced at different conditions of temperature and time of induction. IB were subjected to chemical treatments with surfactants (CTAB; Cetrimide; ARG-12, a derivative surfactant Argenine) and a denaturing agent (guanidine hydrochloride); physical treatment by sonication and the enzymatic treatment with protease native C. procera latex. Electrophoresis assays suggested that two chemical surfactants were effective in solubilizing rCpOsm while not ARG-12. Although these cationic compounds solubilized rCpOsm more than other proteins of IB, while the sonication process samples produced with a greater variety of soluble proteins including rCpOsm. The enzymatic treatment showed that IB proteins are, in some range, digested while rCpOsm did not. All samples were evaluated for action on Colletotrichum gloeosporiodes after dialysis and lyophilization and showed inhibitory activity of spore germination and mycelial growth. However, it was shown that the activity could be related to the solubilising agents. Insoluble proteins obtained from E. coli containing the plasmid integrity, taken as a negative control showed no activity in these assays. The rCpOsm solubilized by CTAB was subjected to chromatography on Ni ++ column (Ni Sepharose 6 Fast Flow) pH 7.0; in hydrophobic media (FenilSepharose CL-4B) and ion exchange (Resource-S). None of the applied protocols resulted in the purification of rCpOsm and these data repeated what was observed previously for rCpOsm purified from Pichia pastoris.